PENGARUH MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Himatul Anisah; Duano Sapta Nusantara; Rohati Rohati (Universitas PGRI Sumatera Barat, 2026)
This study aims to analyze the effect of the Problem Based Learning (PBL) model on improving students’ mathematical problem-solving ability through a Systematic Literature Review (SLR) using the PRISMA protocol. Analysis of 15 relevant articles retrieved from Scopus (2015–2025) revealed a significant publication growth of 780% with a compound annual growth rate (CAGR) of 24%, reaching its peak in the period 2024–2025. VOSviewer analysis identified four main themes: problem solving, effect, development, and concept. PBL demonstrated a significant positive effect, with an N-gain of 0.708 in the experimental group compared to 0.22 in the control group (p<0.001). Effective factors in implementing PBL include problem orientation, structured group learning, integration of real-life contexts, metacognition, collaboration, and reflection. PBL also enhances affective aspects such as positive attitudes, perseverance, and student motivation. This study concludes that PBL is an effective learning model and is recommended for improving students’ mathematical problem-solving ability across various educational levels.